A fuzzy Based Under-Frequency Load Shedding Scheme for islanded distribution network connected with DG - Mokhlis, Hazlie; Laghari, J.A.; Bakar, A.H.A.; Karimi, M. (Praise Worthy Prize, 2012)
The frequency of power system is very sensitive to load changing when operating in islanded mode. This may causes overloading or loss of generation cases. Under-Frequency Load Shedding (UFLS) Scheme is commonly applied to stabilize the frequency during these cases. Conventional UFLS scheme operates successfully in interconnected grid system and may not work well when applied to DG based system operating in islanded mode. This paper presents a new fuzzy logic based under-frequency load shedding scheme implemented on mini hydro type-DG operating in islanded mode. The proposed strategy is based on frequency, rate of change of frequency and load prioritization. In proposed UFLS scheme, a fuzzy logic load shedding controller (FLLSC) with Load Shed Controller Module (LSCM) is modelled. FLLSC measures amount of load to be shed and LSCM shed the respective load to stabilize frequency. The proposed scheme is validated on different event-based and response-based cases. Simulation results show that proposed scheme is effective in shedding optimal number of loads while stabilizing the frequency.